UNDER THE SEA - Sido, Barbi (Bath, UK : Really Decent Books Ltd., 2019)
A first concepts book introducing your child to ocean animals. Perfect for little minds and hands.
Early learning guide : First words, Stimulates the senses, Recommended age- 1+ years -- Back cover
Age 1+.
Keywords: Children's early learning material; Picture book for children; Marine animals -- Juvenile literature; Marine animals -- Pictorial works -- Juvenile literature; Board books